2011
DOI: 10.1016/j.carbpol.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonionic surfactant and acidity on chitosan nanofibers with different molecular weights

Abstract: a b s t r a c tBlend solutions of chitosan (Cs) and poly(ethylene oxide) (PEO) at different acidities were electrospun to produce membranes of nanofibers with different diameters. The use of polysorbate surfactant Tween 20 to improve functionality of these nanofibers was studied. The procedure was as follows: 5% (w/v) of two high deacetylation degree Cs with different molecular weights (Mw = 148 kDa and 68 kDa) were dissolved in solutions with different acetic acid concentrations (10%, 50% and 90% (v/v)) then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…1 indicated that the zero-shear viscosity of 2.5% chitosan was 0.43 Pa s while, a 2.5 wt% composite solution of chitosan/PEO with 75:25 ratio showed a higher viscosity (0.73 Pa s) than both of its precursor solutions. This is possibly due to the strong interactions between chitosan and large expanded PEO chains which make sufficient entanglement and facilitate electrospinning (Pakravan et al, 2011;Ziani et al, 2011). The addition of PHMB to chitosan solution with PEO slightly reduced the viscosity to 0.65 Pa s. However, increasing PHMB content to 1 mM, led to reduction in the zero shear viscosity by 10% (0.58 Pa s).…”
Section: Rheological Behaviormentioning
confidence: 76%
See 4 more Smart Citations
“…1 indicated that the zero-shear viscosity of 2.5% chitosan was 0.43 Pa s while, a 2.5 wt% composite solution of chitosan/PEO with 75:25 ratio showed a higher viscosity (0.73 Pa s) than both of its precursor solutions. This is possibly due to the strong interactions between chitosan and large expanded PEO chains which make sufficient entanglement and facilitate electrospinning (Pakravan et al, 2011;Ziani et al, 2011). The addition of PHMB to chitosan solution with PEO slightly reduced the viscosity to 0.65 Pa s. However, increasing PHMB content to 1 mM, led to reduction in the zero shear viscosity by 10% (0.58 Pa s).…”
Section: Rheological Behaviormentioning
confidence: 76%
“…Pure chitosan did not form fibers and only beads or drops in the range of 328 nm were deposited. It has been hypothesized that the repulsive forces between ionic groups within polymer backbone increased due to the application of a high electric field during electrospinning restricted formation of continuous fibers and produced particles (Pakravan et al, 2011;Ziani et al, 2011). Addition of PEO to the chitosan solution, disrupt the self-association of chitosan chains by formation of additional hydrogen bondings between its hydroxyl groups and water molecules.…”
Section: Morphology Of Nanofibersmentioning
confidence: 98%
See 3 more Smart Citations